Immersive Virtual Reality in Alleviating Pain and Anxiety in Children During Immunization in Primary Care: A Pilot Randomized Controlled Trial - Chang, Zi Ying; Kang, Gary Chun-Yun; Koh, Eileen Yi Ling; Fong, Rodney Jin Kai; Tang, Jiasheng; Goh, Chi Keong; Tan, Ngiap Chuan (Frontiers in Pediatrics, 2022)
Background: Paediatric immunization is often associated with significant fear and anxiety among the children and their parents. Their distress may potentially affect their adherence to the childhood immunization schedule and the acceptance of other recommended vaccines by physicians. Objectives: The study primarily aimed to assess the feasibility of using immersive virtual reality (VR) during immunization in children in primary care. The secondary aim was to determine the effectiveness of immersive VR in alleviating pain and anxiety among children, reduction of anxiety of their parents and attending nurses during immunization compared to usual care without VR. Methods: A pilot open-label randomized control trial was conducted at a public primary care clinic in Singapore. Thirty children, aged 4-10 years were randomised to an intervention group (n=15) using VR and a control group (n=15) without VR during immunization. Feasibility was assessed by the response rate to the use of VR. The Faces Pain Scale-Revised (FPS-R) and the Children’s Fear Scale (CFS) were used to determine their pain and anxiety respectively. The anxiety level of their accompanying parents and attending nurses were evaluated using Visual Analogue Scale (VAS) prior and post-immunization of these children. Results: One child refused to use the VR equipment, constituting a rejection rate of 6.7% (1/15) but no adverse event occurred in the intervention arm. The overall response rate of 88% (30/34) when the parents were approached to participate in the study, indicating feasibility of using VR in childhood immunization. In the intervention group compared to the control group, the change in scores for CFS (median -1, IQR -2 to 0; P=.04), parental VAS (median -4, IQR -5 to -1; P=.04) were significantly decreased. After immunization, nurses scored favourably for VR, in terms of simplicity (median 9.5, IQR 5.72 to 10; P=.01), acceptability (median 10, IQR 5 to 10; P=.005) and willingness to use VR in the future (median 10, IQR 5 to 10; P=.02). Conclusions: Immersive VR is feasible, safe and effective in alleviating anxiety among the children and parents . Nurses viewed the application of VR in childhood immunization favorably.